Gender- and age-related features of the association between TP53 Pro72Arg polymorphism and primary open-angle glaucoma - S.Iu. Mogilevskyy; S.V. Ziablitsev; L. I. Denisiuk (Ukrainian Society of Ophthalmologists, 2016)
Background: The TP53 gene is directly related to the development of primary open-angle glaucoma (POAG). There have been inconsistent reports regarding increased risk of POAG and the C allele (72Pro) of the TP53 codon 72 polymorphism. Purpose: To identify associations, if any, between TP53 Pro72Arg polymorphism and presence of POAG in patients of different genders and age groups. Materials and Methods: The study group comprised 172 patients (78 men (45%) and 94 (55 %) women) diagnosed with POAG, and the control group comprised 98 individuals (46 men (47 %) and 52 women (53 %)) without POAG. The mean age of study participants was 57.3±1.1 years at the time of the examination for POAG. Results: In males with POAG, the frequencies of the 72Pro allele and of the Pro72Pro genotype of the ТР53 gene were found to be increased (1.4 times, р = 0.014 and 2.2 times, р = 0.039, respectively) compared to the relevant controls. The presence of the 72Pro allele in males (as well as in females) was associated with POAG. Male carriers of the 72Pro allele had a 1.87 (p (?2) = 0.021) times higher risk for the disease. Elevated frequencies of the 72Pro allele and the Pro72Pro genotype of TP53 codon 72 polymorphism were specific for POAG males older than 60 years, which had a 2.786 times higher risk for the disease (p (?2) = 0.019) compared to the relevant controls. Elevated frequency of the 72Pro allele, as well as decreased frequency of the 72Arg allele was more specific for POAG females younger than 60 years compared to the relevant controls. Female 72Pro allele carriers younger than 60 years had a 2.30 (p (?2) = 0.034) times higher risk for the disease compared to the relevant controls. Conclusions: The presence of the 72Pro allele in males was associated with POAG. POAG males older than 60 years had a 2.786 times higher risk for the disease compared to the relevant controls. The presence of the 72Pro allele in females was associated with POAG. Female 72Pro allele carriers younger than 60 years had a 2.30 times higher risk for the disease compared to the relevant controls.